EPCO-14. DECIPHERING DIFFERENTIATION HIERARCHIES, HERITABILITY AND PLASTICITY IN HUMAN GLIOMAS VIA SINGLE-CELL MULTI-OMICS. (9th November 2020) - Gaiti, Federico; Chaligne, Ronan; Silverbush, Dana; Schiffman, Joshua; Weisman, Hannah; Kluegel, lloyd; Gritsch, Simon; Deochand, Sunil; Richman, Alyssa; Klughammer, Johanna; Biancalani, Tommaso; Muus, Christoph; et al.
Abstract: Human diffuse gliomas are incurable malignancies, where cellular state diversity fuels tumor progression and resistance to therapy. Single-cell RNA-sequencing (scRNAseq) studies recently charted the cellular states of the two major categories of human gliomas, IDH-mutant gliomas (IDH-MUT) and IDH-wildtype glioblastoma (GBM), showing that malignant cells partly recapitulate neurodevelopmental trajectories. This raises the central questions of how cell states are encoded epigenetically and whether unidirectional hierarchies or more plastic state transitions govern glioma cellular architectures. To address these questions, we generated multi-omics single-cell profiling, integrating DNA methylation (DNAme), transcriptome and genotyping of 1, 728 cells from 11 GBM and IDH-MUT primary patient samples. Direct comparison of the methylomes of distinct glioma cell states revealed Polycomb repressive complex 2 (PRC2) targets DNAme as a key switch in the differentiation of malignant GBM cells. In contrast, dissecting aberrant circuits of hyper-methylation and gene expression in IDH-MUT gliomas, we observed a decoupling of the promoter methylation-expression relationship, with disruption of CTCF insulation and enhancer vulnerability which increases with cellular differentiation. To define cell state transition dynamics directly in patient samples, we generated high-resolution lineage histories of glioma cells using heritable DNAme changes, and projected the scRNAseq-derived cell states onto the lineage trees. This analysis demonstrated that cell states are heritable across malignant gliomas and, while in IDH-MUT differentiation far outpaces de-differentiation, GBM harbors a higher degree of cell state plasticity allowing reversion of GBM cells from a differentiated to a stem-like state. Overall, our work provides detailed insights into gliomagenesis, dissecting the epigenetic encoding, regulatory programs, and dynamics of the cellular states that drive human gliomas. Importantly, it also carries significant translational implication, as the high degree of de-differentiation in GBM challenges the paradigm of therapeutically targeting glioma stem-like cells to deprive tumors of their ability to regenerate.